Fragile X syndrome screening in pregnant women and women planning pregnancy shows a remarkably high FMR1 premutation prevalence in the Balearic Islands. Issue 8 (22nd June 2016) - Alfaro Arenas, Ramona; Rosell Andreo, Jordi; Heine Suñer, Dami; ,
Abstract : There are no reported studies to determine incidence of Fragile X Syndrome (FXS) in women within the Spanish population. For this reason, together with the high incidence of FXS in the general population, the exclusively maternal expansion, the familial and social impact of the syndrome, and the ease of use and level of detection of current PCR‐based techniques, we have conducted a population‐based screening pilot program of which we present here the molecular results. We typed prospectively 3, 413 pregnant and 318 non‐pregnant women and found a prevalence of premutation (PM) carriers of 1 in 106, which is the highest described to date in any population. We also found 230 different alleles of which the most frequent are 10A9A9 (38.4%), 9A9A9 (15.1%), and 10A9 (10.5%). Furthermore, alleles with 0 AGG interruptions or with a pure (uninterrupted) CGG repeat run larger than 34 (presumably more unstable), were more frequent among PM alleles compared to normal alleles. Theà unexpected high frequency of expanded PM alleles in females in the general population makes a very compelling argument for the need for prenatal or preconceptional FXS screening in our community. Furthermore, we find FMR1 triplet primed PCR (TP‐PCR) confidently and precisely determines sizes for both alleles of the CGG repeat in women and offers AGG information which greatly improves CGG expansion risk estimations for genetic counselling. Thus, TP‐PCR is an informative, efficient and robust method for FXS screening in the female population. © 2016 Wiley Periodicals, Inc.